Antitumor activity of a folate receptor-targeted immunoglobulin G-doxorubicin conjugate - Yang T (Dove Medical Press, 2017)
Tan Yang,1,* Ling Xu,1,* Bin Li,1 Weijie Li,1 Xiang Ma,1 Lingling Fan,2 Robert J Lee,3 Chuanrui Xu,1 Guangya Xiang1 1Department of Biopharmaceuticals, School of Pharmacy, 2Stem Cell Center, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China; 3Division of Pharmaceutics and Pharmaceutical Chemistry, College of Pharmacy, The Ohio State University, Columbus, OH, USA *These authors contributed equally to this work Abstract: Development of antibody-drug conjugates (ADCs) is a promising therapeutic strategy for cancer therapy. In this study, folate was conjugated via a polyethyleneglycol (PEG) linker to immunoglobulin G (IgG), which was linked to doxorubicin (DOX), to form a novel ADC folate-PEG-IgG-DOX (FA-PEG-IgG-DOX). The FA-PEG-IgG-DOX showed high targeting efficiency in HeLa and KB cells and significantly improved the uptake and retention of DOX compared with IgG-DOX about 10-fold. Subsequently, FA-PEG-IgG-DOX was shown to have at least 8 times higher antitumor activity than IgG-DOX both in HeLa and KB cells and also induced more apoptosis in those cells than IgG-DOX. Moreover, FA-PEG-IgG-DOX had a 2 times longer circulating time than FA-IgG-DOX, but did not increase the DOX distribution in mouse hearts. Importantly, FA-PEG-IgG-DOX treatment significantly inhibited tumor growth in xenograft mice. Together, our results indicate that FA-PEG-IgG is an effective ADC carrier for delivery of chemotherapeutic agents and that conjugating tumor targeting ligands to antibodies is a promising strategy for producing ADC drugs. Keywords: folate, immunoglobulin G, doxorubicin, antibody-drug conjugate, cancer